Selective Electron Beam Patterning of Oxygen‐Doped WSe2 for Seamless Lateral Junction Transistors. Issue 26 (19th July 2022) - Ngo, Tien Dat; Choi, Min Sup; Lee, Myeongjin; Ali, Fida; Hassan, Yasir; Ali, Nasir; Liu, Song; Lee, Changgu; Hone, James; Yoo, Won Jong
Abstract: Surface charge transfer doping (SCTD) using oxygen plasma to form a p‐type dopant oxide layer on transition metal dichalcogenide (TMDs) is a promising doping technique for 2D TMDs field‐effect transistors (FETs). However, patternability of SCTD is a key challenge to effectively switch FETs. Herein, a simple method to selectively pattern degenerately p‐type (p + )‐doped WSe2 FETs via electron beam (e‐beam) irradiation is reported. The effect of the selective e‐beam irradiation is confirmed by the gate‐tunable optical responses of seamless lateral p + –p diodes. The OFF state of the devices by inducing trapped charges via selective e‐beam irradiation onto a desired channel area in p + ‐doped WSe2, which is in sharp contrast to globally p + ‐doped WSe2 FETs, is realized. Selective e‐beam irradiation of the PMMA‐passivated p + ‐WSe2 enables accurate control of the threshold voltage ( V th ) of WSe2 devices by varying the pattern size and e‐beam dose, while preserving the low contact resistance. By utilizing hBN as the gate dielectric, high‐performance WSe2 p‐FETs with a saturation current of −280 µA µm −1 and on/off ratio of 10 9 are achieved. This study's technique demonstrates a facile approach to obtain high‐performance TMD p‐FETs by e‐beam irradiation, enabling efficient switching and patternability toward various junction devices. Abstract : The authors utilize a selective e‐beam irradiation to pattern the doping profile of oxidized p + ‐WSe2 field‐effect transistors (FETs), overcoming the key challenge of surface charge transfer doping. Seamless lateral junction p‐FETs are realized with high on/off ratio (10 9 ) and saturation current (−280 μ A µm −1 ), which are crucial for designing logic circuits.